Redescription of the brackish water crab Ptychognathus glaber Stimpson, 1858 based on the topotypic material from the Ogasawara Islands and new record of P. lipkei N.K. Ng, 2010 from Japan (Decapoda: Brachyura: Varunidae) - Komai, Tomoyuki; Maenosono, Tadafumi; Saeki, Toshifumi; Naruse, Tohru (Zootaxa, 2021)
Examination of material from various Japanese localities clarified that the estuarine crab Ptychognathus glaber Stimpson, 1858 is possibly restricted to the Ogasawara Islands, Japan. Specimens from the Ryukyu Islands, thought to represent P. glaber, actually represent P. lipkei N.K. Ng, 2010 instead, previously known only from Cebu, the Philippines. Ptychognathus glaber is redescribed in detail, and differentiating characters between it and P. lipkei are reassessed. Previous literature records of P. glaber are reviewed in the light of our findings. Genetic analysis using partial sequences of the mitochondrial 16S rRNA gene suggests that P. glaber is genetically closer to P. ishii Sakai, 1939 than to P. lipkei, and thus P. ishii is also compared morphologically with P. glaber.